函数F=AB+BC,使F=1的输入ABC组合为( )。
A: ABC=010
B: ABC=101
C: ABC=110
A: ABC=010
B: ABC=101
C: ABC=110
C
举一反三
- 函数F =AB +BC,使F=1的输入ABC 组合为 ( )。 A: ABC=000 B: ABC=010 C: ABC=101 D: ABC=110 E: ABC=011 F: ABC=100
- 函数F=AB+BC,使F=1的输入ABC组合为( ) A: BC=000 B: BC=010 C: BC=110 D: BC=101
- 函数Y=AB+BC,使Y=1的输入ABC组合为_________。 A: ABC=000 B: ABC=010 C: ABC=101 D: ABC=110
- 函数F=AB+BC,使F=1的输入ABC组合为( ) A: 000 B: 010 C: 101 D: 110
- 函数F=AB+BC,使F=1的输入ABC组合为( ) A: 000 B: 010 C: 101 D: 110
内容
- 0
函数F=AB+BC,使F=1的输入ABC的取值组合为( )。 A: 000 B: 110 C: 101 D: 010
- 1
函数F=AB+BC,使F=1的输入ABC的取值组合为( )。 A: 000 B: 110 C: 101 D: 010
- 2
函数F=AB+BC,使F=1的输入ABC组合为 A: ABC=100 B: ABC=110 C: ABC=011 D: ABC=000
- 3
函数F=AB+BC,可以使F=1的输入ABC组合为( ) A: ABC=011 B: ABC=110 C: ABC=111 D: ABC=000 E: ABC=100 F: ABC=101 G: ABC=001
- 4
逻辑函数F=AB+BC,使F=1的输入ABC的组合是 A: 001 B: 010 C: 101 D: 110